New Policy Directives for the Host Family Program in Ontario - Deidre Riordon (McMaster University Library Press, 2017)
The Host Family Program is a provincially-funded residential accommodation program that offers adults with developmental disabilities the chance to live with people who can provide care, support and supervision in a family setting. Individuals with developmental disabilities tend to be at a greater risk for neglect and abuse, so it is imperative that legislation be in place to prevent this from happening. The Host Family Program implemented new policy requirements in April of 2016 in order to increase the safety and security of the people who are in the care of host families. Following a sentinel event that occurred in 2012 in Ancaster, Ontario, a coroner's inquest was conducted and subsequent jury recommendations were made. From these the Ministry of Community and Social Services developed the new policy directives. While the Host Family Program provides housing accommodations to approximately 1,500 people, there are many other vulnerable individuals in several other residential programs and on waiting lists. It is worrisome that there is currently no distinct and separate policy in place to protect these individuals from harm. The policy directives for the Host Family Program are a step in the right direction by government, but further policy development must be achieved in order to prevent future tragedies. Le programme des services de relève en famille hôte est un programme de logement financé par la province qui permet aux adultes ayant une déficience intellectuelle de vivre avec des personnes qui peuvent offrir des soins, un soutien et une supervision dans un cadre familial. En général, les personnes ayant une déficience intellectuelle courent un plus grand risque d'être négligées et maltraitées ; il est donc impératif que des lois soient mises en place pour empêcher que cela se produise. Le programme des services de relève en famille hôte a mis en ~oeuvre de nouvelles exigences en avril 2016 afin d'accroître la sûreté et la sécurité des personnes qui vivent dans une famille hôte. Suite à un événement fatal qui a eu lieu à Ancaster, en Ontario, en 2012, une enquête du coroner a été menée et le jury a prescrit plusieurs recommandations. Le ministère des Services sociaux et communautaires a consulté ces recommandations pour développer les nouvelles directives. Même si le programme des services de relève en famille hôte accueille 1.500 personnes, beaucoup de personnes vulnérables relèvent d'autres  programmes de logements  ou sur des listes d'attente, et il est donc inquiétant qu'il n'y ait actuellement aucune politique spécifique  en place pour les protéger. Les nouvelles exigences publiées par le gouvernement pour le programme des services de relève en famille hôte vont dans le bon sens, mais il faut élaborer plus de politiques pour prévenir d'autres tragédies.